Efficiency of protected areas in Amazon and Atlantic Forest conservation: A spatio-temporal view - Sobral-Souza, Thadeu [UNESP]; Vancine, Maurício Humberto [UNESP]; Ribeiro, Milton Cezar [UNESP]; Lima-Ribeiro, Matheus S. (Elsevier, 2018)
The Amazon and Atlantic Forest are considered the world's most biodiverse biomes. Human and climate change impacts are the principal drivers of species loss in both biomes, more severely in the Atlantic Forest. In response to species loss, the main conservation action is the creation of protected areas (PAs). Current knowledge and research on the PA network's conservation efficiency is scarce, and existing studies have mainly considered a past temporal view. In this study, we tested the efficiency of the current PA network to maintain climatically stable areas (CSAs) across the Amazon and Atlantic Forest. To this, we used an ecological niche modeling approach to biome and paleoclimatic simulations. We propose three categories of conservation priority areas for both biomes, considering CSAs, PAs and intact forest remnants. The biomes vary in their respective PA networks' protection efficiency. Regarding protect CSAs, the Amazon PA network is four times more efficient than the Atlantic Forest PA network. New conservation efforts in these two forest biomes require different approaches. We discussed the conservation actions that should be taken in each biome to increase the efficiency of the PA network, considering both the creation and expansion of PAs as well as restoration programs.
Keywords: Climate change; Conservation biology; Niche modeling; Paleoclimate simulation; Tropical forests